The structure and toxicity of winter cyanobacterial bloom in a eutrophic lake of the temperate zone - Wejnerowski, Łukasz; Rzymski, Piotr; Kokociński, Mikołaj; Meriluoto, Jussi (Ecotoxicology (London), 2018)
Winter cyanobacterial blooms have become increasingly common in eutrophic lakes advocating a need for their monitoring and risk assessment. The present study evaluated the toxicity of a winter cyanobacterial bloom in a eutrophicated freshwater lake located in Western Poland. The bloom was dominated by potentially toxic species: Planktothrix agardhii , Limnothrix redekei , and Aphanizomenon gracile . The toxin analysis revealed the presence of demethylated forms of microcystin-RR and microcystin-LR in ranges of 24.6–28.7 and 6.6–7.6 µg/L, respectively. The toxicity of sampled water was further evaluated in platelet-rich plasma isolated from healthy human subjects using lipid peroxidation and lactate dehydrogenase assays. No significant adverse effects were observed. The present study demonstrates that toxicity of some winter cyanobacterial blooms in the temperate zone, like that in Lubosińskie Lake, may not exhibit significant health risks despite microcystin production.